Circular Causation Model: Intellectual Capital, Islamic Financial Risk, And Islamic Financial Performance Relationship At Islamic Commercial Banks - Azwirman; Meutia, Inten; Novriadi; Yaacob, Zulnaidi (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The aim of this research is to investigate how the intellectual capital, Islamic financial risk, and Islamic financial performance are interconnected within Islamic commercial banks, using a circular causation model. The study's population comprises all Islamic commercial banks listed by Bank Indonesia from 2015 to 2020. The sample selection method employed is purposive sampling. A total of 48 annual reports from various companies were analyzed using the circular causation model, and the causal relationships between these variables were explored through simultaneous equations and dynamic Two Stage Least Square (2SLS) methods. The analytical software utilized for this study is EVIEWS 9. The selected samples encompass Bank Syariah Mandiri, Bank Panin Syariah, Bank BNI Syariah, Bank BRI Syariah, Bank Bukopin Syariah, Bank Mega Syariah, Bank Muamalat, and Bank BCA Syariah, for the period spanning from 2015 to 2020.The research findings suggest that Intellectual Capital has no effect on Profit Sharing Ratio and Zakat Performance Ratio. Additionally, the financing, liquidity, capital, and operational risk do not exert any effect on Zakat Performance Ratio, Profit Sharing Ratio, or Equitable Distribution Ratio. From a Circular Causation perspective (TSR), Zakat Performance and Profit-Sharing Ratio, as well as the Equitable Distribution Ratio do not exert any effect on Intellectual Capital, financing, liquidity, capital, and operational risk. Furthermore, Intellectual Capital did not have an effect on financing, capital, and operational risk. Conversely, financing, capital, and operational do not affect Intellectual Capital.